Personalized medicine in inflammatory cardiomyopathy. (2nd February 2018) - Neupane, Balram; Zhou, Qifeng; Gawaz, Meinrad; Gramlich, Michael
Inflammatory cardiomyopathy is the result of persistent myocardial inflammation which can arise from both infectious or noninfectious causes. While most patients with acute myocarditis recover, up to 20% develop inflammatory cardiomyopathy with chronic heart failure. The interaction between host factors and factors of the agent that triggered myocardial inflammation must be considered to fully understand the individual mechanism of disease. Several inflammatory biomarkers, histology, immunohistochemistry, advanced imaging technologies as well as molecular high-throughput sequencing techniques help to identify disease pathways and to establish a comprehensive, individualized treatment approach, which can include anti-inflammatory medication, antiviral drugs and heart failure therapy. This might help to prevent transition from acute inflammation to persistent heart failure and to restore cardiac function.